Utilising microsimulation to estimate new marginal returns to education: Ireland 1987-2005 - Darragh Flannery; Cathal O'Donoghue (Institute for the Study of Labor (IZA), 2011)
In this paper we utilise microsimulation techniques in the form of an income generation model and a tax/benefit model to estimate both the fiscal and net private return to education at a marginal level. This is carried out empirically using Irish data across the period 1987-2005 and is the first study to utilise these techniques in such a manner. The results indicate that a more generous tax/benefit system, combined with a greater state burden of the cost of education over this period may have helped increase the individual's return to education, while reducing the state return from investing in education. The methodology employed allows us to specifically analyse the impact of various components of the tax/benefit system upon these returns across time and show the role of income tax changes upon the return to education for the individual and the state.
urn:nbn:de:101:1-201104134305
Keywords: I22; I28; 330; returns to education; microsimulation; income generation model; Bildungsertrag; Marginalanalyse; Steuer; Sozialtransfer; Einkommensteuer; Mikrosimulation; Bildungsfinanzierung; Irland